Perancangan Ulang Tata Letak Fasilitas Menggunakan Metode ARC, ARD dan SRD pada PT. XYZ - Alorinda Zantia Maubila; Dindha Aprilia Kinanti; Moch Bahrul Ulum; Ida Kusnawati Tjahjani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
An inappropriate facility layout may hinder coordination and reduce operational effectiveness within a company. This study aims to redesign the facility layout at PT. XYZ using the Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Space Relationship Diagram (SRD) methods. A descriptive quantitative approach with Systematic Layout Planning (SLP) was employed. Data were collected through observation, interviews, and documentation of the existing facility layout. The results indicate that the closeness relationships among facilities can be systematically identified through ARC and subsequently visualized using ARD and SRD as the basis for developing the proposed layout. The proposed layout places facilities with high activity relationships in closer proximity, making it more suitable for the company’s operational needs. The findings demonstrate that SLP is an effective approach for facility layout redesign.